Biorefinery and Stepwise Strategies for Valorizing Coffee By-Products as Bioactive Food Ingredients and Nutraceuticals - Miguel Rebollo-Hernanz; Yolanda Aguilera; Alicia Gil-Ramírez; Vanesa Benítez; Silvia Cañas; Cheyenne Braojos; Maria A. Martin-Cabrejas (Applied Sciences, 2023)
Coffee production generates significant amounts of by-products, posing challenges for waste management in the industry. Recent research has revealed that coffee by-products are rich in bioactive compounds suitable to produce functional food ingredients and nutraceuticals. In this review, we explore biorefinery strategies for extracting and utilizing bioactive compounds from coffee by-products, including the production of bio-based chemicals and materials, as well as the extraction of phenolic compounds, antioxidants, and dietary fiber for food applications. We propose a stepwise approach for the development of functional food ingredients and nutraceuticals from coffee by-products, covering the identification of needs, comprehensive characterization, in vitro and in vivo research, unraveling the mechanism of action, food and nutraceutical formulation, sensory analysis, shelf-life stability, scale-up, randomized control trials, and biostatistics and bioinformatic integration. Additionally, we discuss the market potential, regulatory issues, and technological innovation surrounding the commercialization of coffee by-product-based products. Emphasizing the importance of regulatory compliance and sustainability in the coffee industry, this review highlights the potential of coffee by-products to be transformed from waste into valuable functional food ingredients and nutraceuticals, offering a promising avenue for waste reduction and promoting sustainability in the coffee industry.